EKOLEKSIKON DALAM KUMPULAN LAGU DAERAH SUKU KUTAI, KALIMANTAN TIMUR: KAJIAN EKOLINGUISTIK - Rahman, Abdur; Yudista, Rensiana; Barack, Choirunnisa Fadilla; Wahyuni, Ian (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2024)
This research aims to discuss the language styles and natural lexicon found in the lyrics of Kalimantan regional songs, especially Kutai. This research is a type of library research with an ecolinguistic approach. The method used is a qualitative method with descriptive analysis. The material objects are the lyrics of regional songs from the Kutai tribe, East Kalimantan, namely the lyrics of the songs "Burung Enggang Meriesta" by Djuriansyah, "Belarut di Sungai Mahakam" by Djuriansyah, "Meharit" by Djuriansyah, "Buah Bolok" by Masdari Ahmad, and "Nasi Bekepor” by Ismed Rizal. The formal object is ecolinguistic theory. The unit of analysis includes words, phrases, clauses and sentences contained in the songs. The results of the study show that there are personification and repetition figures of speech in the regional songs of the Kutai tribe. Apart from that, there is also a natural lexicon, namely the flora lexicon and fauna lexicon. This can be interpreted to mean that the Kutai regional song lyrics utilize figures of speech with flora and fauna lexicons as their attraction.